E-Commerce Analysis of Customer Satisfaction and Hotel Reservation Quantity in Cilacap Regency - Berlilana Berlilana; Fiby Nur Afiana (Universitas Amikom Purwokerto, 2020)
This research aims to determine the effects of e-commerce implementation on customer satisfaction and room reservation quantity. The data is obtained from questionnaires distribution and analyzed using Multiple Regression Analysis where F-Test and T-Test tested the 168 samples of 290 population. From the result of analysis, Partial test on customer satisfaction shows that the three variables have t count> t table, the independent variable is quality of use (X1), namely 8,132> 1,974; the independent variable information quality (X2), namely 2.609> 1.974; the independent variable of interaction quality (X3) is 2.956> 1.974, so each H1 is accepted. Regarding the room reservation level, the partial test shows the three variables have t count> t table, the independent variable is the quality of use (X1), namely 2.181> 1.974; the independent variable information quality (X2), namely 2.021 <1.974; the independent variable of the quality of the interaction (X3), namely 3.497> 1.974, so H1 is accepted. It can be concluded that the usability quality (X1), quality of information (X2), and quality interaction (X3) have significant effects on customer satisfaction (Y1) and room reservation quantity (Y2). Specifically, the quality of interaction shows a significant effect on the room reservation quantity as well as the quality of information and interaction on customer satisfaction. Based on this research, it can be concluded that the quality of interaction and quality of information have a positive effect on customer satisfaction, and only the interaction variable has a positive effect on the quantity of hotel room reservation.